Monetary Policy in a New Keynesian Model with Endogenous Growth - Barbara Annicchiarico; Lorenza Rossi (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2012)
We study monetary policy in a New Keynesian (NK) model with endogenous growth and knowledge spillovers external to each firm. We find the following results: (i) technology and government spending shocks have different effects on growth; (ii) disinflationary monetary policies entail positive effects on growth; (iii) the optimal long-run inflation rate is zero; (iv) the Ramsey dynamics implies deviation from full inflation targeting in response to technology and government spending shocks; (v) the optimal operational rule is backward looking and responds to inflation and output deviations from their long-run levels.
Keywords: E32; E52; O42; 330; Monetary Policy; Endogenous Growth; Disinflation; Ramsey Problem; Optimal Simple Rules